2022
DOI: 10.1039/d2rp00070a
|View full text |Cite
|
Sign up to set email alerts
|

Examining relationships between chemistry anxiety, chemistry identity, and chemistry career choice in terms of gender: a comparative study using multigroup structural equation modelling

Abstract: Although there are numerous chemistry-related careers within the STEM fields, chemistry-related careers are not well regarded. High school is a critical time for developing students’ career choices. Previous studies suggest...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 96 publications
0
2
0
Order By: Relevance
“…This anxiety is, in fact, also closely related to the learning experience in class, as revealed in another CMQ II study by Vedder-Weiss and Fortus (2013) and Zhou et al (2019) The teacher can reduce anxiety in learning chemistry. One way is collaborative active learning (Guo et al, 2022). An active learning environment can increase students' interest and competence in chemistry (Hendrikson, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This anxiety is, in fact, also closely related to the learning experience in class, as revealed in another CMQ II study by Vedder-Weiss and Fortus (2013) and Zhou et al (2019) The teacher can reduce anxiety in learning chemistry. One way is collaborative active learning (Guo et al, 2022). An active learning environment can increase students' interest and competence in chemistry (Hendrikson, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The results suggested that the correlations between all variables were significant (Fig. 2) (Guo et al, 2022).…”
Section: Descriptive Statistics and Bivariate Correlationsmentioning
confidence: 93%
“…Studies showed that choosing a STEM career is influenced by personal factors (e.g., interest, self-efficacy, perception of the subject) and environmental-social factors (e.g., family, teachers, peers, social background) (Chakraverty and Tai, 2013;Venville et al, 2013;Lo ´pez et al, 2023). Many studies have been conducted on elementary and high school students' choice of STEM learning and career (Guo et al, 2022;Huangfu et al, 2022;Ofek-Geva et al, 2023), with fewer focusing on university education and the factors that influence undergraduate students to choose to major specifically in chemistry. (Ogunde et al, 2017;Avargil et al, 2020;Archer et al, 2023).…”
Section: Introductionmentioning
confidence: 99%